(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensor networks (WSNs) plays a vital role in many real-time applications due to its topology structure, network size and communication. Data privacy, node path planning and integrity are the essential factors that optimizes the network efficiency and trust. Since, most of the traditional WSN path planning are independent of integrity and node trust computation, it is difficult to provide privacy and robust path planning in large WSNs. In order to overcome these issues, a hybrid trust-based node integrity verification and privacy preserving model is implemented for the dynamic WSNs. In this model, a hybrid ACO based node trust probability and path planning is proposed along with new local update and global update measures. Experimental results proved that the present trust based model has better runtime, hash variation and privacy preserving metrics than the traditional WSNs cluster based authentication protocols.